B1 ;
Cho A =\(\left(\frac{x^2-x+7}{x^2-4}+\frac{1}{x+2}\right)\)/\(\left(\frac{x+2}{x-2}-\frac{x-2}{x+2}+\frac{2x}{4-x^2}\right)\)
a,Rút gọn A
b,,tìm x khi A =1
B2;Cho biểu thức
B=\(\left(\frac{2+x}{2-x}-\frac{2-x}{2+x}-\frac{4x^2}{x^2-4}\right)\)/\(\frac{x+3}{2-x}\)
với x\(\ne\)+-2;x\(\ne\)-3
a,rút gọn B
b,tìm x nguyên để B nguyên
Bài 1
ĐK \(\hept{\begin{cases}x\ne2\\x\ne-2\end{cases}}\)
A =\(\left(\frac{x^2-x+7}{\left(x+2\right)\left(x-2\right)}+\frac{1}{x+2}\right):\left(\frac{x+2}{x-2}-\frac{x-2}{x+2}-\frac{2x}{\left(x+2\right)\left(x-2\right)}\right)\)
\(=\frac{x^2-x+7+x-2}{\left(x+2\right)\left(x-2\right)}:\frac{x^2+4x+4-x^2+4x-4-2x}{\left(x+2\right)\left(x-2\right)}\)
\(=\frac{x^2+5}{\left(x+2\right)\left(x-2\right)}.\frac{\left(x+2\right)\left(x-2\right)}{6x}=\frac{x^2+5}{6x}\)
b , \(A=1\Rightarrow\frac{x^2+5}{6x}=1\Rightarrow x^2-6x+5=0\Rightarrow\orbr{\begin{cases}x=1\\x=5\end{cases}\left(tm\right)}\)
Vậy x=1 hoặc x=5
Bài 2.
a. \(B=\frac{\left(2+x\right)^2-\left(2-x\right)^2+4x^2}{\left(2+x\right)\left(2-x\right)}:\frac{x+3}{2-x}\)
\(=\frac{4x^2+8x}{\left(2+x\right)\left(2-x\right)}.\frac{2-x}{x+3}=\frac{2x}{x+3}\)
b. \(B=\frac{2x}{x+3}=2-\frac{6}{x+3}\)
B nguyên \(\Leftrightarrow x+3\inƯ\left(-6\right)\Rightarrow x+3\in\left\{-6;-3;-2;-1;1;2;3;6\right\}\)
\(\Rightarrow x\in\left\{-9;-6;-5;-4;-2;-1;0;3\right\}\)
Vậy \(x\in\left\{-9;-6;-5;-4;-2;-1;0;3\right\}\)thì B nguyên